Teacher Readiness for Integrating Artificial Intellegence in Integrated ADLX Learning at Islamic Secondary School - Haerani, Rina Hesti; Priyambada, Galih (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2026)
ABSTRACT The rapid development of artificial intelligence (AI) has significantly influenced teaching and learning practices in schools. However, empirical studies examining teacher readiness to integrate AI within value-based and integrated learning models remain limited, particularly in Islamic integrated secondary schools. This study aims to analyze the readiness of general subject teachers at SMPIT Ummul Quro to integrate AI into Integrated ADLX learning, which emphasizes meaningful activities, discussion, practice, and ethical reflection. A quantitative descriptive research design was employed involving 33 general subject teachers as respondents. Data were collected using a validated questionnaire covering four dimensions of teacher readiness: technological competence, pedagogical readiness, ethical awareness, and institutional support. The data were analyzed using descriptive statistical techniques to obtain a comprehensive overview of teachers’ readiness levels. The results indicate that teachers’ readiness to integrate AI into Integrated ADLX learning is at a moderate level. Teachers demonstrate positive attitudes and relatively high ethical awareness regarding the use of AI in educational contexts. However, their technological competence and pedagogical application of AI remain limited, particularly in designing learning activities that effectively utilize AI to support instructional objectives. In addition, institutional support in the form of structured training programs and clear operational policies for AI integration has not been fully optimized. These findings suggest that effective AI integration in learning does not rely solely on teachers’ acceptance and ethical awareness but also requires systematic professional development and sustained institutional support. This study contributes empirical evidence to the discourse on AI integration in integrated Islamic secondary education and provides practical implications for school leaders in developing teacher capacity-building programs that align technological innovation with pedagogical effectiveness and ethical values.